Preliminary Valuation Activity of Calotropis gigantea L. Extracts against Several Insect Pests - Khasanah, Nur; Martono, Edhi; Trisyono, Y. Andi; Wijonarko, Arman (Universitas Gadjah Mada, 2022)
Calotropis gigantea produces secondary metabolites. Some toxicity tests on several pest species had been conducted, yet the most susceptible pest species towards C. gigantea extract is still unknown. This study aims to determine the susceptible insect species and study the behavior of susceptible insects to C. gigantea extract. The test methods used in this research were leaf dipping and spraying upon four insect pest species of different orders (Bactrocera carambolae [Diptera: Tephritidae], Nilapavata lugens [Hemiptera: Delphacidae], Sitophilus zeamais [Coleoptera: Curculionidae], and Plutella xylostella [Lepidoptera: Plutellidae]). The concentration used to determine susceptible insects was 25 g.L-1 and control. Deterrence test of susceptible insects using a choice test and no-choice for 1.5 hours observed every five minutes. Five replication were used for each concentration. Behavioral test of susceptible insects using dietary toxicity test. Five bok choy leaf disc was immersed into solutions for 1 minute and air-dried on a petri dish. Observations were carried out for 12 hours with an observation period of every 1.5 hours. A leaf dipping test for 12 hours with an observation period of every 1.5 hours using the feed method. The concentrations used were 12.5 µgL-1and control. The concentration used was the toxicity test of C. gigantea leaf extract 25, 12.50, 6.25. 3.12, 1.56, 0.78, 0.39, 0.19, 0.09, 0.04 µgL-1. P. xylostella was considered a more susceptible test insect towards C. gigantea leaf extract than B. carambolae, N. lugens, and S. zeamais. C. gigantea leaf extract showed a toxic and feeding deterrent to P. xylostella larvae. The LC50 value of C. gigantea extract against P. xylostella by dipping was 16.9 µg.l-1 and 18.5 µg.l-1 by spray. The components of C. gigantea leaf extract consist of alkaloid, tannin, phenol, flavonoid, saponin, and terpenoid. The result of the research showed that C. gigantea leaf extract has a toxic and deterrent substance against P. xylostella and potential to control P. xylostella.